PERANCANGAN SISTEM INFORMASI FRONT OFFICE HOTEL BERBASIS WEB DENGAN PEMODELAN UML DAN INTEGRASI SMART ROOM - Muhammad Fadli; Rifka Simbolon; Izza Maulida Santoso; Valdi Mughni Budiman; Hadori Rosadi; Budi Rahman (LPPM Universitas Abdurrab, 2026)
The rapid advancement of digital technology has significantly transformed the hospitality industry, particularly in enhancing front office services as the primary point of interaction between guests and the hotel. This study aims to design a web-based front office information system integrated with smart room technology, utilizing Unified Modeling Language (UML) as the modeling approach. The developed system, named SIFOHSMART, combines administrative data management functions with intelligent service features based on the Internet of Things (IoT). The main innovation of this system lies in the automatic notification feature from smart panels in guest rooms to the front office, enabling real-time detection and handling of complaints. This research adopts a prototyping methodology, including literature review, field observations, stakeholder interviews, user requirements analysis, UML diagram design (use case and activity), and system testing. The results demonstrate that the system improves operational efficiency, accelerates service response time, and supports data-driven decision-making. The contribution of this study extends beyond technological innovation by incorporating a human-centered design approach that considers usability and convenience for hotel staff. This system has the potential to serve as a reference model for developing adaptive and sustainable hotel information systems in the modern hospitality sector.